Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Given that \(\cos \theta = \frac{24}{25}\) and \(\theta\) lies in quadrant IV, we need to find the exact values for \(\sin 2\theta\), \(\cos 2\theta\), and \(\tan 2\theta\).
### a. \(\sin 2\theta\)
We start with the double angle formula for sine:
[tex]\[ \sin 2\theta = 2 \sin \theta \cos \theta \][/tex]
First, we find \(\sin \theta\). Since \(\theta\) is in quadrant IV, \(\sin \theta\) will be negative. Using the Pythagorean identity:
[tex]\[ \sin^2 \theta + \cos^2 \theta = 1 \][/tex]
we know \(\cos \theta = \frac{24}{25}\), so:
[tex]\[ \sin^2 \theta + \left(\frac{24}{25}\right)^2 = 1 \][/tex]
[tex]\[ \sin^2 \theta + \frac{576}{625} = 1 \][/tex]
[tex]\[ \sin^2 \theta = 1 - \frac{576}{625} \][/tex]
[tex]\[ \sin^2 \theta = \frac{625}{625} - \frac{576}{625} \][/tex]
[tex]\[ \sin^2 \theta = \frac{49}{625} \][/tex]
So, \(\sin \theta = -\frac{7}{25}\) (since \(\theta\) is in quadrant IV).
Now, substituting \(\sin \theta\) and \(\cos \theta\) into the double angle formula:
[tex]\[ \sin 2\theta = 2 \left(-\frac{7}{25}\right) \left(\frac{24}{25}\right) \][/tex]
[tex]\[ \sin 2\theta = 2 \left(-\frac{168}{625}\right) \][/tex]
[tex]\[ \sin 2\theta = -\frac{336}{625} \][/tex]
Thus:
[tex]\[ \sin 2\theta = -\frac{336}{625} \][/tex]
### b. \(\cos 2\theta\)
We use the double angle formula for cosine:
[tex]\[ \cos 2\theta = \cos^2 \theta - \sin^2 \theta \][/tex]
Substituting the known values:
[tex]\[ \cos 2\theta = \left(\frac{24}{25}\right)^2 - \left(-\frac{7}{25}\right)^2 \][/tex]
[tex]\[ \cos 2\theta = \frac{576}{625} - \frac{49}{625} \][/tex]
[tex]\[ \cos 2\theta = \frac{576 - 49}{625} \][/tex]
[tex]\[ \cos 2\theta = \frac{527}{625} \][/tex]
Thus:
[tex]\[ \cos 2\theta = \frac{527}{625} \][/tex]
### c. \(\tan 2\theta\)
We use the double angle formula for tangent:
[tex]\[ \tan 2\theta = \frac{\sin 2\theta}{\cos 2\theta} \][/tex]
Substituting the values we found:
[tex]\[ \tan 2\theta = \frac{-\frac{336}{625}}{\frac{527}{625}} \][/tex]
[tex]\[ \tan 2\theta = \frac{-336}{527} \][/tex]
Thus:
[tex]\[ \tan 2\theta = -\frac{336}{527} \][/tex]
### Summary
Given the information:
[tex]\[ \cos \theta = \frac{24}{25}, \theta \text{ lies in quadrant IV} \][/tex]
we have found:
[tex]\[ \sin 2\theta = -\frac{336}{625} \][/tex]
[tex]\[ \cos 2\theta = \frac{527}{625} \][/tex]
[tex]\[ \tan 2\theta = -\frac{336}{527} \][/tex]
### a. \(\sin 2\theta\)
We start with the double angle formula for sine:
[tex]\[ \sin 2\theta = 2 \sin \theta \cos \theta \][/tex]
First, we find \(\sin \theta\). Since \(\theta\) is in quadrant IV, \(\sin \theta\) will be negative. Using the Pythagorean identity:
[tex]\[ \sin^2 \theta + \cos^2 \theta = 1 \][/tex]
we know \(\cos \theta = \frac{24}{25}\), so:
[tex]\[ \sin^2 \theta + \left(\frac{24}{25}\right)^2 = 1 \][/tex]
[tex]\[ \sin^2 \theta + \frac{576}{625} = 1 \][/tex]
[tex]\[ \sin^2 \theta = 1 - \frac{576}{625} \][/tex]
[tex]\[ \sin^2 \theta = \frac{625}{625} - \frac{576}{625} \][/tex]
[tex]\[ \sin^2 \theta = \frac{49}{625} \][/tex]
So, \(\sin \theta = -\frac{7}{25}\) (since \(\theta\) is in quadrant IV).
Now, substituting \(\sin \theta\) and \(\cos \theta\) into the double angle formula:
[tex]\[ \sin 2\theta = 2 \left(-\frac{7}{25}\right) \left(\frac{24}{25}\right) \][/tex]
[tex]\[ \sin 2\theta = 2 \left(-\frac{168}{625}\right) \][/tex]
[tex]\[ \sin 2\theta = -\frac{336}{625} \][/tex]
Thus:
[tex]\[ \sin 2\theta = -\frac{336}{625} \][/tex]
### b. \(\cos 2\theta\)
We use the double angle formula for cosine:
[tex]\[ \cos 2\theta = \cos^2 \theta - \sin^2 \theta \][/tex]
Substituting the known values:
[tex]\[ \cos 2\theta = \left(\frac{24}{25}\right)^2 - \left(-\frac{7}{25}\right)^2 \][/tex]
[tex]\[ \cos 2\theta = \frac{576}{625} - \frac{49}{625} \][/tex]
[tex]\[ \cos 2\theta = \frac{576 - 49}{625} \][/tex]
[tex]\[ \cos 2\theta = \frac{527}{625} \][/tex]
Thus:
[tex]\[ \cos 2\theta = \frac{527}{625} \][/tex]
### c. \(\tan 2\theta\)
We use the double angle formula for tangent:
[tex]\[ \tan 2\theta = \frac{\sin 2\theta}{\cos 2\theta} \][/tex]
Substituting the values we found:
[tex]\[ \tan 2\theta = \frac{-\frac{336}{625}}{\frac{527}{625}} \][/tex]
[tex]\[ \tan 2\theta = \frac{-336}{527} \][/tex]
Thus:
[tex]\[ \tan 2\theta = -\frac{336}{527} \][/tex]
### Summary
Given the information:
[tex]\[ \cos \theta = \frac{24}{25}, \theta \text{ lies in quadrant IV} \][/tex]
we have found:
[tex]\[ \sin 2\theta = -\frac{336}{625} \][/tex]
[tex]\[ \cos 2\theta = \frac{527}{625} \][/tex]
[tex]\[ \tan 2\theta = -\frac{336}{527} \][/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We appreciate your time. Please come back anytime for the latest information and answers to your questions. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.